Doulas for Childbearing Women. Issue 2 (March 2015) - Ahlemeyer, Jessica; Mahon, Suzanne
<x xml:space="preserve">Abstract</x> Abstract Doulas are sometimes sought to provide support to women during childbirth. Communication between nurses and doulas is essential to work together effectively and promote the best outcomes for the mother and baby. An understanding of the training and certification of doulas and potential roles and benefits of a doula-assisted birth can be the foundation for developing strategies to improve communication and collaboration between doulas and nurses.